Optimizing Regional Budgets Through Accountability in Budget Planning in the Digital Era - Triputra, Dimas Syah Rosa; Marantika, Abshor; Kasmawati, Kasmawati (Dinasti Publisher, 2026)
Study This lift topic optimization of the regional budget through accountability in planning budgeting in the digital age, with variables main ones that include accountability as variables free (measured through dimensions transparency, participation public, and supervision digital -based) and optimization of the regional budget as variables bound (seen from efficiency, effectiveness, and realization budget). This research aims to (1) Analyze influence accountability in planning budget to optimization of the APBD in Kampar Regency in the digital era; (2) Identify factor inhibitors and drivers accountability based technology; (3) formulate recommendation strategic for increase efficiency management finance area. The results of data analysis from study about optimization Budget Regional Revenue and Expenditure (APBD) through accountability in planning Budgeting in the digital era in Kampar Regency. Analysis done in accordance with the mixed-methods method described previously, with Focus on the integration of quantitative data (surveys and secondary data) and qualitative data (interviews and observations). Simulation results based on realistic hypothetical data, assuming collecting data from 300 respondents and documents official 2020-2024.